2023
DOI: 10.1117/1.nph.10.2.025008
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing a two-layer method for hybrid diffuse correlation spectroscopy and frequency-domain diffuse optical spectroscopy cerebral measurements in adults

Abstract: Significance: The sensitivity to extracerebral tissues is a well-known confounder of diffuse optics. Two-layer (2L) head models can separate cerebral signals from extracerebral artifacts, but they also carry the risk of crosstalk between fitting parameters. Aim:We aim to implement a constrained 2L head model for hybrid diffuse correlation spectroscopy (DCS) and frequency-domain diffuse optical spectroscopy (FD-DOS) data and to characterize errors in cerebral blood flow and tissue absorption with the proposed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…[10][11][12] Regardless, it appears that there may be crosstalk between the extracerebral layer thickness and BSR for the three-layer model as well as, to a lesser extent, the two-layer model. 19 We found that CBFi estimated with the homogenous model was significantly positively correlated with TCD blood flow velocities in the MCA obtained on the same day. Given that the TCD and DCS measurements were often acquired hours apart, a lack of correlation between DCS and TCD would be difficult to interpret given the patients' possible hemodynamic instability.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…[10][11][12] Regardless, it appears that there may be crosstalk between the extracerebral layer thickness and BSR for the three-layer model as well as, to a lesser extent, the two-layer model. 19 We found that CBFi estimated with the homogenous model was significantly positively correlated with TCD blood flow velocities in the MCA obtained on the same day. Given that the TCD and DCS measurements were often acquired hours apart, a lack of correlation between DCS and TCD would be difficult to interpret given the patients' possible hemodynamic instability.…”
Section: Discussionmentioning
confidence: 58%
“…13 This trend was independent of the SNR for the integration times that we investigated; however, the pass rate will likely decrease at higher sampling frequencies in which the SNR is significantly reduced because these models have been shown to be highly sensitive to noise. 12,19 One striking, although not surprising, finding was that the pass rate of the multilayer model fitting was significantly influenced by the extracerebral layer thickness. This trend was most prominent in the three-layer model, although it was also seen in the two-layer model.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…One method to account for extracerebral tissue is to switch from the traditional semiinfinite geometry model, which is commonly used in DCS, to a multi-layered (typically two or three-layered) geometry model [85][86][87]. Although this is an effective technique, these models rely on accurate prior knowledge of the optical properties and thickness of each layer.…”
Section: Depth Discrimination Techniquesmentioning
confidence: 99%